Experimental and numerical study on the responses of a transmission tower to skew incident winds. Issue 157 (October 2016) - Deng, H.Z.; Xu, H.J.; Duan, C.Y.; Jin, X.H.; Wang, Z.H.
Abstract: A study on a lattice suspension tower in a four-span transmission line system subjected to skew incident wind forces is presented via experimental and numerical approaches. The purpose of this work is to investigate the response features of the tower especially to the wind not incoming along the structure's principle axes. At the geometric scaling of 1:80, the aeroelastic model is manufactured with scaled rigidity, mass, area projection and frequency. Wind tunnel tests on the model, with and without conductors, are conducted at a variety of incident angles. Then numerical simulations are applied quasi-steadily to figure out an analytical way of interpreting and supplementing experimental results. Such quasi-steady method is generally valid since the tested aerodynamic damping ratios, though scattered, roughly meet the quasi-steady formulae. Results show that for the tower without conductors the dynamic accelerations do not vary significantly with the incident angle either in the r.m.s. values or in the spectral contents, as wind forces on the tower lend dependency on both the along wind and the across wind components of fluctuating winds thus have equivalent magnitudes at different wind incidences. For the tower with conductors, the longitudinal forces on the conductor are quite different from the lateral ones according to the simulated mechanism. As the co-effect of the additional loads and extra damping provided by conductors, dynamic accelerations of the tower show distinct characteristics in different axes and at different wind incidences. Highlights: Responses of tower line system to skew incident winds are studied. Tested aerodynamic damping ratios validate quasi-steady theory. Spatial load model of tower line system to skew incident winds is constructed.